Prevalence of microalbuminuria, arterial hypertension, retinopathy, and neuropathy in patients with insulin dependent diabetes - Parving, Hans-Henrik (1988)
Diabetic nephropathy is the main cause of the increased morbidity and mortality in patients with insulin dependent diabetes. The prevalence of microalbuminuria was determined in adults with insulin dependent diabetes of five or more years' duration that had started before the age of 41. All eligible patients (n=982) attending a diabetes clinic were asked to collect a 24 hour urine sample for analysis of albumin excretion by radio-immunoassay; 957 patients complied. Normoalbuminuria was defined as urinary albumin excretion of ≤30 mg/24 h (n=562), microalbuminuria as 31-299 mg/24 h (n=215), and macroalbuminuria as ≥300 mg/24 h (n=180). The prevalence of microalbuminuria and macroalbuminuria was significantly higher in patients whose diabetes had developed before rather than after the age of 20. The prevalence of arterial hypertension increased with increased albuminuria, being 19%, 30%, and 65% in patients with normoalbuminuria, microalbuminuria, and macroalbuminuria respectively. The prevalence of proliferative retinopathy and blindness rose with increasing albuminuria, being 12% and 1·4%, respectively, in patients with normoalbuminuria, 28% and 5·6% in those with microalbuminuria and 58% and 10·6% in those with macroalbuminuria. An abnormal vibratory perception threshold was more common in patients with microalbuminuria (31%) and macroalbuminuria (50%) than in those with normoalbuminuria (21%). This study found a high prevalence (22%) of microalbuminuria, which is predictive of the later development of diabetic nephropathy. Microalbuminuria is also characterised by an increased prevalence of arterial hypertension, proliferative retinopathy, blindness, and peripheral neuropathy. Thus, urinary excretion of albumin should be monitored routinely in patients with insulin dependent diabetes.